2009
DOI: 10.1523/jneurosci.2041-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Shifts in Local Field Potential Power Spectra Are Correlated with Single-Neuron Spiking in Humans

Abstract: A fundamental question in neuroscience concerns the relation between the spiking of individual neurons and the aggregate electrical activity of neuronal ensembles as seen in local field potentials (LFPs). Because LFPs reflect both spiking activity and subthreshold events, this question is not simply one of data aggregation. Recording from 20 neurosurgical patients, we directly examined the relation between LFPs and neuronal spiking. Examining 2030 neurons in widespread brain regions, we found that firing rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
948
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 898 publications
(1,019 citation statements)
references
References 54 publications
68
948
0
3
Order By: Relevance
“…1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005].…”
Section: Discussionsupporting
confidence: 84%
“…Power decreases in low frequency sensorimotor rhythms are distributed over larger areas of cortex [Crone et al, 1998b;Miller et al, 2007]. These spectral changes are associated with different processes: broadband power change is associated with local neuronal processing [Manning et al, 2009;Miller et al, 2009a], whereas low frequency oscillations reflect an aspect of subcortical-cortical interaction [Brown, 2003;Feige et al, 2005;Pfurtscheller and Lopes da Silva, 1999;Schnitzler et al, 2006]. Functional MRI BOLD change has also been compared with electrocortial stimulation mapping, and has been shown to be adequately sensitive but less specific in predicting electrocortical stimulation sites [Pouratian et al, 2002;Rutten et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…activity (Ray et al, 2008;Ray and Maunsell, 2011;Ray, 2015; similar in nature to the 'broadband power shift' described in Manning et al, 2009), consistently increases around spindles ( Figure 4A). Further, HGP is modulated by spindle phase ( Figure 4B), increasing towards the surface-positive (depth-negative) peak, consistent with previous animal (Peyrache et al, 2011) and human recordings.…”
Section: Introductionsupporting
confidence: 61%
“…18 Importantly, the ECoG electrode grids employed here allowed for a spatial resolution that is on the same order as our fMRI measurements. Studies have shown that power in higher frequencies (440 Hz) correlates well with neuronal firing rates [19][20][21] and also with BOLD signal change. 22,23 The ECoG high-frequency broadband power thus provided a direct measure of electrical activity in confined neuronal ensembles, which we compared with BOLD fMRI measurements.…”
Section: Introductionmentioning
confidence: 99%